Willingness to Pay (WTP) for pipe-water connection in Makululu compound of Kabwe, Zambia - Yordanos Gebremeskel; Nyambe Mubita; Bupe Simuchimba; James Mulenga (African Journal of Environmental Economics and Management, 2017)
The availability of safe drinking water is dependent on better and improved water sources for households. Access to safe drinking water especially piped water is one of the challenges faced by households in Zambia. This study aims to understand the factors that determine the willingness to pay for pipe water connection on low income peri-urban settlements in Zambia. Double bounded questions which have the advantage of including a follow up dichotomous question after the first dichotomous choice question are used. An interval regression model is used to analyze the collected data. The variables of interest are purification, family size, water quality, education and income. The results obtained show that most of these variables have the expected signs. Further, the results suggests that an increase in income will lead to an increase in the willingness to pay to have access to safe drinking water sources. The results also suggest that the distance travelled to fetch water from a community tap and level of household education play a role in the willingness to pay for access to pipe water connection. We estimated that the sample household mean WTP is K283.77 ($38.14) which is roughly 33% of the commercial connection charge.